National Water Governance in Indonesia: An Analysis of Hydroclimatology, Coastal Geodynamics, and Regulatory Reform - Aditya Hafizh Wicaksono; Arifah Rizkiya Nurjanah; Muhammad Raykhan Pandu Wijoyo; Rayhan Harliando (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze national water governance and sovereignty through an integrated literature review combined with a qualitative-descriptive case study approach. The study used 22 national and international scientific articles published between 2014 and 2026 as the primary data source. The analysis was conducted on aspects of hydroclimatology, nutritional vulnerability, coastal geodynamics, environmental economic valuation, water resource regulation, and technological engineering and community adaptation. The analysis results indicate that climate change causes a decrease in water availability, increases public health and nutritional vulnerability, accelerates land subsidence and relative sea level rise in coastal areas, and causes economic losses due to water resource degradation. On the other hand, the implementation of water governance still faces various institutional obstacles despite being supported by Law Number 17 of 2019 concerning Water Resources. Various technological innovations and community-based adaptations show potential in supporting the provision of clean water and sustainable water resource conservation. This study provides a comprehensive overview of the condition of national water resources and policy recommendations for realizing sustainable and equitable water governance